Iraqi EFL Instructors’ and Learners’ Attitudes towards the Application of ChatGPT in Using Cohesive Devices in Narrative Texts at University Level - Ahmed, Ban Shihab; Salem, Khalid Nayef (Journal of Tikrit University for Humanities, 2025)
Recently many learners have started using ChatGPT in many disciplines of life or different sciences learning where it showed its importance in facilitating learning and saving time and efforts. This study aims at shedding the light on the use of ChatGPT application at university level by EFL learners at Garmian University. The Sample of the study are one hundred students and twenty instructors from English Department at College of Languages. The study tries the answer the question: ‘ can learners’ get benefit from ChatGPT application while learning how to use cohesive devices in narrative texts ? what is the role of ChatGPT and to what extend ? to answer the question of the study a questionnaire has been constructed that involves twenty items. The items of the questionnaire refer to the techniques or strategies used by learners’ and teachers’ to produce accurate or coherent texts and compare it with ChatGPT. This study is limited to university level learners , the use of Chat GPT application, narrative texts. After collecting data and analyzing them statistically some conclusions are drawn.